EFFICIENCY OF LIGHT-WEIGHT CONCRETE WALLS FROM POROZED LEAKED ITEMS CONCRETE (Spectrum Journal of Innovation, Reforms and Development, 2022)
The article is devoted to ways to improve the humidity and thermal conditions of lightweight concrete walls. The research data on improving the thermal properties of porous claydite-concrete modified with the K-9 additive with heat power waste - ash are presented. An effective way to improve the moisture regime of walls using a moisture meter is recommended.